IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) DI DESA KANTANAN KECAMATAN BOKAT KABUPATEN BUOL - UM Armin, Sri Yanti (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This study aims to analyze the implementation of the Self-Help Housing Stimulus Assistance Program (BSPS) in Kantanan Village, Bokat District, Buol Regency. The BSPS program is a government initiative to improve housing quality for low-income communities through the provision of stimulus assistance for the renovation of inadequate housing. The research method used is a qualitative approach, with data collection through interviews, observation, and document studies. The findings indicate that although the program has successfully improved the housing quality of the recipients, there are several challenges in its implementation, such as limited funds, lack of socialization, and coordination issues among related parties. Additionally, active community participation plays a significant role in the smooth execution of the program. This study recommends the need to enhance the capacity of village governments in managing the program and to strengthen communication between the central government, local governments, and communities to improve the effectiveness of the BSPS program in the future.